A constraint programming primer - Gilles Pesant (Elsevier, 2014)
The purpose of this short paper is to give a reader acquainted with combinatorial optimization enough background in Constraint Programming to appreciate the other papers in this special issue. We will cover modeling, inference, and search. Whenever appropriate we will make an effort to relate some of the concepts to that of other computational approaches. Those interested to learn more about this computational approach will also find some pointers to the literature on recent advances in the area.